Essays on Lobbying and Club Formation - Joshi, Priyanka (2020)
Chapter 1 of this doctoral thesis studies that whether micro-targeting (MT) is an effective tool as a lobbying strategy to influence policy and/or election outcomes. Interest groups (IGs) have a membership base who can be sent group-specific messages (MT) on behalf of the political candidate. The IG demands policy favours in exchange for facilitating MT. We investigate how exchange of policy favours for MT influences the election outcome, and hence, policy outcomes. It is shown that IGs who are opposed to the candidate’s ideal policy could effectively use MT to change policy outcomes to their advantage. But IGs who have same ideal policy as the candidate’s do not find MT effective. However, interestingly, their presence in the political system itself can affect the influence other IGs exert.